Literasi Keuangan, Financial Technology dan Perilaku Keuangan Mahasiswa - Siskawati, Erly Nabila; Ningtyas, Mega Noerman (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2022)
The purpose of this study was to analyze the effect of financial literacy and financial technology toward the financial behavior. This type of research is explanatory research using a sample of 389 undergraduate students at UIN Maulana Malik Ibrahim Malang from the 2018-2021 class. We collected data through an online questionnaire (google form) and analyzed it using SEM-PLS with the help of SmartPLS 3 software. The results indicates that financial literacy had a positive significant effect on student financial behavior and financial technology had a negative and significant effect on student financial behavior.